Respuesta :
For this case we have that the sum of 3 consecutive integers is 24, if we represent by means of an equation we have:
[tex]x + (x + 2) + (x + 4) = - 24\\x + x + 2 + x + 4 = -24\\3x + 6 = -24\\3x = -24-6\\x = \frac {-30} {3}\\x = -10[/tex]
Thus, the three consecutive numbers are:
[tex]x = -10\\x = -10 + 2= -8\\x = -10 + 4 = -6[/tex]
Answer:
-10,-8,-6
Answer: [tex]-10,-8,-6[/tex]
Step-by-step explanation:
Let be:
[tex]x[/tex], [tex]x+2[/tex] and [tex]x+4[/tex] the three consecutive even integers whose sum is -24
Then, we can write this expression:
[tex]x+(x+2)+(x+4)=-24[/tex]
Now, we must solve for "x":
[tex]3x+6=-24\\\\3x=-24-6\\\\3x=-30\\\\x=\frac{-30}{3}\\\\x=-10[/tex]
Then you get that the others integers are:
[tex]x+2=-10+2=-8[/tex]
[tex]x+4=-10+4=-6[/tex]
Therefore, the three consecutive even integers whose sum is -24 are:
[tex]-10,-8,-6[/tex]